Phenotyping Before Starting Treatment in COPD?. (4th May 2017) - Siafakas, Nikolaos; Corlateanu, Alexandru; Fouka, Evangelia
ABSTRACT: Chronic Obstructive Pulmonary Disease (COPD) is a heterogeneous and complex disease with great morbidity and mortality. Despite the new developments in the managements of COPD, it was recognized that not all patients benefit from the available medications. Therefore, efforts to identify subgroups or phenotypes had been made in order to predict who will respond to a class of drugs for COPD. This review will discuss phenotypes, endotypes, and subgroups such as the frequent exacerbator, the one with systemic inflammation, the fast decliner, ACOS, and the one with co-morbidities and their impact on therapy. It became apparent, that the "inflammatory" phenotypes: frequent exacerbator, chronic bronchitic, and those with a number of co-morbidities need inhaled corticosteroids; in contrast, the emphysematous type with dyspnea and lung hyperinflation, the fast decliner, need dual bronchodilation (deflators). However, larger, well designed studies clustering COPD patients are needed, in order to identify the important subgroups and thus, to lead to personalize management in COPD.